SOFT MASSAGE USING VIRGIN COCONUT OIL CAN REDUCE UREMIC PRURITUS IN PATIENTS WITH CHRONIC KIDNEY DESEASE - Asmawati Asmawati; Rizka Velia; Pauzan Efendi (Poltekkes Kemenkes Banten, 2026)
Patients undergoing hemodialysis experience pruritus characterized by itching that interferes with comfort, causing skin damage and infection. The purpose of this study was to determine the effect of gentle massage using coconut oil to reduce uremic pruritus in patients with chronic renal failure. The study design was a quasi-experimental study with a pre-post-test design with a control group. The sampling technique used purposive sampling; the number of samples was 36 respondents, with each group having 18 people. The intervention group was given a gentle massage using coconut oil, while the control group was only given coconut oil. The assessment of pruritus used the 5D Itch Scale. Data analysis used a paired t-test with a significance level of α ≤ 0.05. The results showed a decrease in the average degree of uremic pruritus in the intervention group by 3,444 and in the control group by 2,222, with a mean difference of 1.222. The results of the Mann-Whitney U test (p 0.000 < α ≤ 0.05) indicate that there is a difference in the average degree of pruritus. It means that there is an effect of soft massage using Virgin Coconut Oil (VCO) on the reduction of uremic pruritus in patients with chronic kidney disease at RSUD Dr. M Yunus Bengkulu. Soft massage using VCO needs to be recommended to reduce itching symptoms due to increased uremia in patients with kidney failure.